THE ROLE OF MEDIA ADVERTISING AND WORD OF MOUTH ON THE PURCHASE DECISION OF MINISO PRODUCTS IN PALEMBANG CITY (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
Miniso has been discussed and mentioned on Twitter and Instagram, among other social media platforms. This demonstrates the enthusiasm of social media users who follow Miniso and apply it as an interesting conversation starter. Miniso has also been successful in reaching 1.8 million potential users who use their personal mobile devices to discuss subjects regarding retail. These findings demonstrate that Miniso has been successful in generating a large number of impressions through promotional activities on the social media sites mentioned above. Furthermore, the purpose of this study is to determine whether media advertising and word-of-mouth influence consumers' purchase decisions in Palembang City. 120 respondents completed online surveys that were sent via Google Forms. The data was processed by quantitative methods. Results show that: (1) Media Advertising has a positive influence on purchasing decisions. (2) Word of Mouth has a positive effect on purchasing decisions. This study can serve as a resource for other researchers conducting related research as well as an assessment tool for the Miniso corporation.
Keywords: Media Advertising; Word of Mouth; Purchase Decision; Miniso